COMBINATION OF FeCl3 AND Fe3O4 AS A MAGNETIC COAGULANT FOR CONGO RED REMOVAL - Asaf K Sugih; Muhammad A Deiza; Safri F Nurmawan; Susiana Prasetyo; Daniel Tan; Hans Kristianto (Universitas Trisakti, 2025)
Water pollution remains a critical environmental issue, necessitating efficient treatment technologies, among which, coagulation is still widely applied due to its effectiveness in removing colloidal particles and organic pollutants. Inorganic coagulants remain a preferred coagulant despite drawbacks such as excessive sludge formation and long settling times. To address these limitations, the integration of magnetic nanoparticles to form magnetic coagulants has emerged as a promising strategy. Aims: This study was aimed to investigate the effectiveness of the FeCl3 - magnetite (Fe3O4) combination as a magnetic coagulant for the removal of Congo red from synthetic wastewater. Methodology and results: The influence of key parameters, including pH (3-8), coagulant dose (4-44 mL/L), magnetite dose (0-200 mg/L), and initial dye concentration (50-100 mg/L), was systematically evaluated. Coagulation experiment was done by using a standard jar test apparatus. The settling kinetic was evaluated by using pseudo-first and second-order kinetic model. Conclusion, significance and impact study: It was found that pH 6, coagulant dose of 20 mL/L FeCl3 0.5 M, and magnetite dose of 150 mg/L gave the best coagulation efficiency with 95% removal of 50 mg/L Congo red wastewater. Furthermore, the settling kinetics showed a good suitability with non-linear pseudo-second order-model kinetics. Results demonstrated that FeCl3-Fe3O4 as a magnetic coagulant significantly improved floc formation, settling efficiency, and overall pollutant removal.